In situ manipulation of perpendicular magnetic anisotropy in half-metallic NiCo2O4 thin film by proton insertion. (1st October 2022) - Wada, T.; Namiki, W.; Tsuchiya, T.; Kan, D.; Shimakawa, Y.; Higuchi, T.; Terabe, K.
Abstract: Herein we report the manipulation of perpendicular magnetic anisotropy (PMA), a very important technique for spintronics devices, which is achieved in an all-solid-state redox (reduction/oxidation) device. The device consisted of NiCo2 O4 (NCO) thin film with a c -axis orientation and a proton-conducting polymer (Nafion). The PMA of NCO can be manipulated in situ with low voltage ( V  ≤ 0.7 V) due to the utilization of a proton-conducting solid electrolyte. The magnetic anisotropy variation was quantitatively evaluated by an anomalous Hall measurement. The magnetic anisotropy field of the NCO thin film was successfully manipulated in the range of 5%, although the rotation of the easy axis of magnetization was not observed. This modulation is attributed to the strain and electronic configuration variation by proton insertion. This manipulation method for PMA with the solid electrolyte enables a variety of reservoir states and contributes to lower power consumption and high-precision machine learning.